Pengaruh model pembelajaran inkuiri terbimbing terhadap kemampuan berpikir kritis matematis siswa pada fase E SMK negeri 3 Pekanbaru - Puspita, Iwa; Indriati, Mefa; Wahyuni, Astri; Anggraini, Lilis Marina (IKIP Siliwangi, 2024)
The objective of this study is to assess the effect of guided inquiry learning polas on the mathematical critical thinking abilities of students in phase E at SMK Negeri 3 Pekanbaru. The research employs a Bukanequivalent Control Group Design, focusing on the population of phase E students at the institution. A random sampling method was utilized to select two classes, with class X BP 1 designated as the experimental group and class X BP 2 as the control group. The assessment tools consisted of sebelum tes and sesudah tes essay questions designed to measure critical thinking skills. Hypothesis testing was conducted using a bukan-parametric data analysis technique for comparing two averages, specifically the Mann-Whitney U test. The results of the hypothesis test indicated a significance value of Asymp.Sig (2-tailed) at 0.014, which is less than the threshold of 0.05 (0.014 < 0.05). Consequently, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted, leading to the conclusion that guided inquiry learning polas significantly influence students' mathematical critical thinking skills.